Answer:
Step-by-step explanation:
a1 = 6
a2 = 10
a3 = 14
The next member of the sequence is 4 more than the current sequence. Therefore d = 4
a1 = 6
d = 4
n = 13
an = a1 + (n - 1)*d
an = 6 + (n - 1)*4
a_13 = 6 + 12*4
a_13 = 6 + 48
a_13 = 54
Answer:
6x^2 + 4x
Step-by-step explanation:
g(x) + f(x)
= -8x^2 - 3x + 5 + 2x^2 + 7x - 5
= -8x^2 + 2x^2 - 3x + 7x + 5 - 5
= - 6x^2 + 4x
here is your answer. Please like it rate it and mark me as brainly.
The Law of Cosines would be your best bet here, since the unknown side is opposite the known angle 110 degrees.
|AC|^2 = (8 in)^2 + (23 in)^2 - 2(8 in)(23 in)*cos 110 degrees
= 64 in^2 + 529 in^2 - (368 in^2)*(-0.342)
= 593 in^2 + 126 in ^2 approximately
= 719 in^2 approximately
Then the length of side AC is approx. √(716 in^2) = 27 in